Role of Mitochondria in Retinal Pigment Epithelial Aging and Degeneration - Tong, Yao; Zhang, Zunyi; Wang, Shusheng (Frontiers in Aging, 2022)
Retinal pigment epithelial (RPE) cells form a monolayer between the neuroretina and choroid. It has multiple important functions, including acting as outer blood-retina barrier, maintaining the function of neuroretina and photoreceptors, participating in the visual cycle and regulating retinal immune response. Due to high oxidative stress environment, RPE cells are vulnerable to dysfunction, cellular senescence, and cell death, which underlies RPE aging and age-related diseases, including age-related macular degeneration (AMD). Mitochondria are the powerhouse of cells and a major source of cellular reactive oxygen species (ROS) that contribute to mitochondrial DNA damage, cell death, senescence, and age-related diseases. Mitochondria also undergo dynamic changes including fission/fusion, biogenesis and mitophagy for quality control in response to stresses. The role of mitochondria, especially mitochondrial dynamics, in RPE aging and age-related diseases, is still unclear. In this review, we summarize the current understanding of mitochondrial function, biogenesis and especially dynamics such as morphological changes and mitophagy in RPE aging and age-related RPE diseases, as well as in the biological processes of RPE cellular senescence and cell death. We also discuss the current preclinical and clinical research efforts to prevent or treat RPE degeneration by restoring mitochondrial function and dynamics.